Characteristics study of post weld heat treatment in SA 387 grade 22 steel by cladding using gas tungsten arc welding process. (2021) - Britto Joseph, G.; Valarmathi, T.N.; John Rajan, A.; Murugesan, G.; Prabhakaran, R.
Abstract: SA387 Grade 22 steel material is designed for high mechanical strength and high pressure applications. Residual stress is the unwanted phenomenon in cladded SA387 Grade 22 steel in power plant and gas refineries applications. This residual stress can be reduced by the post weld heat treatment process. Similarly corrosion is another problem because of the reaction with the elements in the environment. These problems may be solved by imparting with a layer of corrosion resistant material deposition by means of cladding. Cladding is an economic solution to those problems. But the lifetime of SA387 Grade 22 steel has been reduced due to poor corrosion resistance against subsea water and residual stress. So the essential thickness of the SA387 Grade 22 steel is reduced due to corrosion and it may cause failure of the product used for high pressure applications. In this experiment, the reduced thickness of SA387 Grade 22 steel specimen is compensated by ER80S-B2 electrode material using gas tungsten arc welding (GTAW) process. ER80S-B2 electrode material provides resistance to reabsorption of moisture and in addition to this a high corrosion resistance ERNiCrMo2 material has been deposited over ER80S-B2 welded material by gas tungsten arc welding (GTAW). After deposition on the remanufactured material, the specimen is tested for its effectiveness in resisting corrosion to withstand subsea power plant and gas refineries applications.